Redundant Sudoku rules. Issue 3 (May 2014) - DEMOEN, BART; GARCIA DE LA BANDA, MARIA
Abstract The rules of Sudoku are often specified using 27 all_different constraints, referred to as the big constraints. Using graphical proofs and exploratory logic programming, the following main and new result is obtained: Many subsets of six of these big constraints are redundant (i.e., they are entailed by the remaining 21 constraints), and six is maximal (i.e., removing more than six constraints is not possible while maintaining equivalence). The corresponding result for binary inequality constraints, referred to as the small constraints, is stated as a conjecture.